In silico approach: Prediction of ADMET, molecular docking, and QSPR of secondary metabolites in Mangroves - Didi Nurhadi Illian, Anita Puspa Widiyana, Ani Riani Hasana, Hilda Maysarah, Shofiyah Sabilah Al Mustaniroh, Mohammad Basyuni (Journal of Applied Pharmaceutical Science, 2022)
Mangrove plants are known to produce various secondary metabolites (SMs) such as polyisoprenoids (dolichol and polyprenol), emodin, and luteolin to show anticancer, anti-inflammatory, antiviral, and antibacterial activities. This study aimed to predict the multiple activities of the SMs of mangroves based on several enzymes that utilize the in silico method. The properties of absorption, distribution, metabolism, excretion, and toxicity for emodin, luteolin, polyprenol C80, dolichol-17 (C85), and dolichol-20 (C100) displayed variation. Prediction for Lipinski’s rule showed that emodin and luteolin have lower molecular weight than polyprenol C80, dolichol C85, and dolichol C100. Emodin and luteolin were further docked with cyclooxygenase-2, beta-lactamase, CYP450-dependent 14-alpha demethylase, 3C-like protease, and P-glycoprotein as protein targets using the Molegro Virtual Docker Ver.5.5 approach. In comparison to celecoxib, ketoconazole, clavulanic acid, remdesivir, and verapamil, emodin and luteolin had higher rerank scores. The quantitative structure–property relationships depicted that the electronic parameter, highest occupied molecular orbital (EHOMO), was the physical chemistry parameter that influenced the total clearance. The present findings emphasized that emodin and luteolin from the SMs of mangroves have multiple activities as potent inhibitors of cancer cells and bacterial infections.
Keywords: Emodin, luteolin, dolichol, polyprenol, polyisoprenoids, mangrove, in silico